2015
DOI: 10.4038/tare.v17i1.5296
|View full text |Cite
|
Sign up to set email alerts
|

Training needs of women vegetable farmers in Akinyele local government area of Oyo state, Nigeria

Abstract: Key words: Women farmers, Training needs, Vegetable production fact that information do not always trickle from the husbands to their wives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The study also found that the two religions mostly practiced in the study area were Islam (49.3%) and Christianity (46.4%). This is in line with Yekinni and Oguntade [9].…”
Section: Respondents' Personal Characteristicssupporting
confidence: 91%
“…The study also found that the two religions mostly practiced in the study area were Islam (49.3%) and Christianity (46.4%). This is in line with Yekinni and Oguntade [9].…”
Section: Respondents' Personal Characteristicssupporting
confidence: 91%
“…Its headquarters is located at Moniya. It has latitude of 7°28` and 7°31` and longitude 3°53` and 3°57` [27]. The Local Government Area is five hundred and seventy five square kilometres (575km 2 ) with twelve poling wards and a projected population of 297, 600 as at 2016 from the 2006 national population census [28].…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The major occupations of the people residing in the area are farming, carpentry, trading, marketing, food processing as well as carving work. Crop such as oil palm, cassava, maize, yam, pepper, cucumber, water melon, tomatoes, plantain and okra are mostly grown in the area [29,27].…”
Section: Description Of the Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Its headquarters is located at Moniya. It has latitude of 7 0 28` and 7 0 31` and longitude 3 0 53` and 3 0 57` (Yekinni & Oguntade 2014). The whole Local Government Council area is five hundred and seventy five square kilometres (575km 2 ) with twelve polling wards and a projected population of 297, 600 as at 2016 from the 2006 national population census (NPC, 2006…”
Section: Study Areamentioning
confidence: 99%